Emerging Capital Markets and Globalization : The Latin American Experience - de la Torre, Augusto (Washington, DC: World Bank, 2012)
The book should stimulate a vigorous discussion on how to best revise the reform agenda for capital market development in emerging economies going forward. This effort should involve not only country authorities but also academics and advisers from multilateral agencies such as the World Bank. The complexities highlighted in the book invite intellectual modesty, eclecticism, and constant attention to country specificity. While it does not provide detailed policy prescriptions, the book does point to issues that cannot be ignored and puts forward provocative questions for the policy debate. The policy discussion in the book is particularly interesting with respect to the following aspects: internationalization of stock markets and local currency debt markets. This paper contains the following headings: whither capital market development; developments in capital markets; factors behind the development and internationalization of capital markets; and whither the reform agenda.